Spatial distribution and determinants of unskilled birth attendance in Ethiopia: spatial and multilevel analysis - Gizaw Sisay Belay; Tsion Mulat Tebeje (Scientific Reports)
Abstract Deliveries performed by unskilled birth attendants is a concern in low-and middle-income countries such as Ethiopia. Unskilled birth attendants may lack the necessary medical knowledge and skills to handle potential complications during child birth. Hence, this study was aimed to assess spatial variation and associated factors of unskilled birth attendance in Ethiopia. This study used a total weighted sample of 7579 women who had a live birth in the five years preceding the survey obtained from EDHS 2016 data. ArcGIS 10.7 software was used to detect areas with a high prevalence of unskilled birth attendance in Ethiopia. Besides, a multilevel logistic regression analysis was done to identify associated factors of unskilled birth attendance. The spatial distribution analysis of unskilled birth attendants was significantly varied across the regions in the country with the significant hotspot areas in the eastern Somali, western Gambela, central and eastern Amhara, southwestern Oromia, eastern border of SNNP regions were detected. In the multilevel multivariable logistic regression model; women in age group (25–34), women attained primary and above educational level, women in the middle and richest household wealth status, mass media exposure, ANC visits, region, place of residence and health insurance coverage were significantly associated with unskilled birth attendance. The geospatial distribution of UBAs was varied across the regions of the country. Maternal age group, education level, rural residence, ANC visits, mass media exposure, wealth status, health insurance coverage and barriers in accessing healthcare service were determinant factors of unskilled birth attendance. Therefore, mothers who had no educational level, not covered by health insurance, women from poor households’ economic status, women from rural areas, and women who had no ANC visit should be given priority in terms of resource allocation including skilled personnel and access to healthcare facilities.